Melacak Akar Pemikiran Nu Dalam Menetapkan Hadis Sebagai Hujjah Perpektif Michel Foucault - Pipin Armita (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2017)
NU always cite a Hadith of the Prophet to issue a statute of law. Reviewing the Hadith in NU traditions and understanding is exciting and unique. This uniqueness can also be seen on NU tradition of Hadith when they set it as proof when deciding religion contemporary issues. If the attempt is seen by Foucault’s theory, hadith what be NU choice as evidence is a form of power relations and knowledge. If the efforts seen with Foucault’s theory, the hadith which has been selected as a proof (hujjah) is a form of power and knowledge relation. This pa pe r e xa m i ne s how   t he   root s t hought of   NU i n t he   de t e rm i na t i on of the Hadith as proof by analysis genealogu approach and archeological method on Foucault theory carried “power and knowledge relations”. Base on this theory, to know a root thought of NU in determination of the hadits as proof (hujjah), the impor- tant thing to do is: (1) conducting a genealogical approach to trace the roots of the thought of NU, (2) using the method of assignment as the basis for the NU archeological on Hadith, (3) with the approach of the genealogy and the archeol- ogy method, then a discourse can be presented. With the advent of the discourse, it wi l l  be a nswe re d how t he  root s t hought of  NU i n t he  de t e rm i na t i on of the Hadith as proof.[NU senantiasa mencantumkan hadis nabi untuk mengeluarkan suatu ketetapan hukum. Mengkaji hadis dalam tradisi dan pemahaman NU merupakan hal yang menarik dan unik. Keunikan ini juga dapat dilihat pada usaha NU memposisikan hadis sebagai hujjah saat memutuskan persoalan-persoalan agama kontemporer. Jika usaha tersebut dilihat dengan teori Foucault, maka pilihan NU tentang hadis yang dipilih sebagai hujjah merupakan bentuk relasi kuasa (power) dan pengetahuan (knowledge). Tulisan ini mengkaji bagaimana akar pemikiran NU dalam penetapan hadis sebagai hujjah dengan analisis pendekatan genealogi dan metode arkeologi yang diusung Foucault dalam teorinya ‘relasi kuasa dan pengetahuan’. Berdasarkan teori tersebut, untuk mengetahui sebuah akar pemikiran NU dalam penetapan hadis sebagai hujjah, hal yang penting dilakukan adalah: (1) melakukan pendekatan genealogi untuk melacak akar pemikiran NU, (2) menggunakan metode arkeologis NU sebagai dasar penetapan hadis, (3) dengan adanya pendekatan genealogi dan metode arkelogi, maka sebuah wacana dapat dimunculkan. Dengan munculnya wacana tersebut, maka akan terjawab bagaimana akar pemikiran NU dalam penetapan hadis sebagai hujjah tersebut.]